PENGARUH MODEL PBL BERBANTUAN MEDIA FUN THINKERS BOOK TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA KELAS IV SD - Ariyani, Qori; Prihatiningtyas, Nindy Citroresmi; Basith, Abd. (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to: (1) describe differences in fourth-grade students’ creative thinking skills between the experimental and control classes; (2) determine the magnitude of the effect of the Problem-Based Learning (PBL) model assisted by the Fun Thinkers Book media on students’ creative thinking skills; and (3) describe the implementation of the PBL model supported by the media. The research employed a quantitative approach using a posttest-only control group design. The sample was selected through purposive sampling, with Class IV B as the experimental group and Class IV C as the control group. Data were collected using a creative thinking skills test and an observation sheet to assess the implementation of the learning process. Data analysis was conducted using statistical techniques. The results indicated that: (1) there were differences in students’ creative thinking skills between the experimental and control groups; (2) the PBL model assisted by the Fun Thinkers Book had a substantial effect on improving students’ creative thinking skills; and (3) the average implementation of the learning process was categorized as very good. In conclusion, the PBL model supported by the Fun Thinkers Book is effective in enhancing students’ creative thinking skills.